TRAINING FOR THE PREPARATION OF DIGITAL TEACHING MATERIALS DURING THE COVID-19 PANDEMIC FOR PALU CITY CHEMICAL MGMP - Rahmawati, Sitti; Hamzah, Baharuddin; Afadil, Afadil; Sangkota, Vivi Diah (LPPM Univ. Ibn Khaldun Bogor, 2023)
During the Covid-19 Pandemic, there has been a fundamental change in the implementation of chemistry learning. Face-to-face lectures and laboratory practice to accommodate the connectedness of the three levels of representation can no longer be carried out. Chemistry learning is fully replaced through online learning. The Chemistry MGMP in Palu City realizes the importance of making various efforts so that the chemistry learning process runs well in terms of delivering learning material and carrying out practicums in the laboratory. One application that can be used by combining various learning media that have been used by chemistry teachers (among others: the zoom application, WhatsApp, Google Class Room, LMS, etc.) is using Ice Cream Screen Recorder. There were 40 participants in the training who were chemistry teachers who were members of the Palu City High School Chemistry MGMP group. Activities carried out in the form of training and mentoring are carried out with a participatory model. Community service activities for the Palu City Chemistry Subject Teacher Consultation (MGMP) partners in the preparation of digital teaching materials during the Covid pandemic have been carried out well thanks to good cooperation with various parties. This is illustrated by the output in the form of ice cream-based digital teaching materials and flipbooks that the participants have made from the results of this community service training and mentoring. The final result of this service is according to the expected target, namely the existence of digital chemistry teaching materials that utilize the Ice Cream Recorder application used in chemistry learning.